EXAMINATION TECHNIQUES AND METHODS IN ADVANCED ACCOUNTING. - Burton, Norman L. (The Accounting Review, 1942)
Intelligent consideration of the variety of techniques available for the purpose of testing a person's understanding of a subject presupposes agreement with respect to the nature of the accomplishment expected from its study. Since it is the purpose to review the methods, which may be used to examine students in courses in advanced accounting, it is essential, therefore, that accounting teachers be clear about what they expect such students to have gained through their study. It seems obvious that a person who is pursuing an advanced course in any subject may be presumed to have successfully completed work that is not only preliminary but also prerequisite to it. Even in an elementary course there must be stages of progress, and it is doubtful if universal agreement could be obtained concerning the exact altitude of the plane that separates an advanced course in accounting from an elementary one. It is logical to expect more ground to be covered in a six-hour course than in a four-hour course; on the other hand, the coverage in the six-hour course may be no more extensive, but merely more thorough within a given range than in the four-hour course.